Increased soluble (pro)renin receptor protein by autophagy inhibition in cultured cancer cells. (1st June 2020) - Endo, Moe; Ohba, Koji; Sato, Shigemitsu; Yokota, Yurina; Takahashi, Kazuhiro
Abstract: (Pro)renin receptor ((P)RR) regulates the renin–angiotensin system and functions as an essential accessory subunit of vacuolar H + ‐ATPase. There is accumulating evidence that shows close relationship between (P)RR and autophagy. Soluble (P)RR consisting of the extracellular domain of (P)RR is generated from (P)RR by proteolytic enzymes. The aim of the present study was to clarify the influence of autophagy inhibition on soluble (P)RR expression in cancer cells. Autophagy was inhibited by treatment of bafilomycin A1 or chloroquine in MCF‐7 and A549 cells for 72 hr. Western blot analysis showed that protein levels of soluble (P)RR were markedly elevated by autophagy inhibition, whereas no noticeable increases were observed in full‐length (P)RR. Secretion of soluble (P)RR into the medium was increased dose‐dependently by bafilomycin A1 or chloroquine. Autophagy inhibition was confirmed by enhanced accumulation of autophagy‐related proteins, LC3, p62 and LAMP1 in intracellular vesicles. Increased amount of soluble (P)RR by autophagy inhibition was decreased by site‐1 protease inhibitor, whereas no noticeable increase in site‐1 protease immunoreactivity was observed in cells with autophagy inhibition by immunocytochemistry. These findings suggest that soluble (P)RR protein accumulates by autophagy inhibition, possibly because of the reduced degradation of soluble (P)RR in the intracellular vesicles during autophagy inhibition. Abstract : The present study has shown that intracellular protein levels of soluble (pro)renin receptor are elevated by autophagy inhibition in cultured cancer cells. Autophagy inhibition may cause a reduced degradation of soluble (pro)renin receptor protein in the intracellular vesicles, and increases its accumulation and subsequent secretion by exocytosis. The finding suggests that soluble (pro)renin receptor is a novel biomarker which reflects the status of autophagy inhibition in cancer cells.